2012
DOI: 10.1111/cge.12063
|View full text |Cite
|
Sign up to set email alerts
|

Aging in Rett syndrome: a longitudinal study

Abstract: Little is known about the aging process of people with specific syndromes, like Rett syndrome (RTT). Recognition of the clinical and behavioral characteristics of the adult RTT is needed in order to improve future management of the RTT girl and counseling of parents. In association with the Dutch RTT parent association, a 5-year longitudinal study was carried out. The study population consisted of 53 adult women with a clinical diagnosis of RTT. Postal questionnaires were sent, including demographic features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
42
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 37 publications
(111 reference statements)
17
42
3
Order By: Relevance
“…A number of cohort studies have examined overall health in patients with Rett syndrome, and have found high overall prevalence of a history of epilepsy. The Dutch cohort includes data on 53 individuals collected in 2007, and 37 of these had follow-up data in 2012 (Halbach et al, 2013). Among these, 76% had a history of seizures, but 54% of those with seizures had been seizure-free at some point for at least 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cohort studies have examined overall health in patients with Rett syndrome, and have found high overall prevalence of a history of epilepsy. The Dutch cohort includes data on 53 individuals collected in 2007, and 37 of these had follow-up data in 2012 (Halbach et al, 2013). Among these, 76% had a history of seizures, but 54% of those with seizures had been seizure-free at some point for at least 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far only two studies conducted in the Netherlands (2007: n = 53, 2012: n = 37) [7] and Italy (n = 84) [8] have specifically examined health in adults with Rett syndrome. Overall, general health was reported to be good.…”
Section: Introductionmentioning
confidence: 99%
“…However epilepsy was found to be highly prevalent in both the Dutch (93%) and the Italian cohorts (82%), and while improvement in seizure activity with age was noted for some women [8], some remained difficult to treat and the majority required medications for control of seizures. A post-adolescence decline in gross motor skills has been reported in some [7,9] but not all women with Rett syndrome [7]. Gross motor capabilities are influenced by the type of mutation present in the MECP2 gene and are generally poorer in those requiring surgical correction for scoliosis [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations